Analysis of Bone Height Changes after Maxillary Sinus Augmentation with Simultaneous and Delayed Placement of Dental Implants: A Clinical and Radiographic Study. Issue 6 (27th July 2015) - Yin, Lihua; Yu, Zhanhai; Chen, Zhuofan; Huang, Baoxin; Zhang, Kailiang; Zhou, Ailing; Li, Xiangxin
Abstract: Purpose: To retrospectively assess the changes of the vertical height of the maxillary sinus floor after augmentation with simultaneous and delayed placement of implants. Materials and Methods: In total, 38 patients with 76 implants were involved; vertical bone height of the sinus floor was radiographically measured at different stages including preoperation, immediately postsurgery, 6 and 12 months postsurgery, and 6 and 24 months postfunctional loading. Results: Sinus augmentation significantly increased vertical bone height of the sinus floor for both the simultaneous and delayed groups. The survival rate was 100% in the simultaneous group and 95.46% in the delayed group. For simultaneous placement, the vertical bone height of the sinus floor at 6 and 12 months postsurgery was significantly less than that immediately postsurgery. For both groups, augmented bone height of the sinus floor showed significant decrease from 6 months to 24 months postfunctional loading. The mean value of final bone augmentation was 5.85 mm for simultaneous placement and 5.80 mm for delayed placements. Conclusion: Sinus augmentation with simultaneous and delayed placement of implants led to similar survival rates and bone augmentation. Resorption of augmentative bone was evident at 24 months postfunctional loading in both cases.